Effect of neurofeedback training on auditory evoked potentials’ late components reaction time: a placebo-control study - Stanković, Ivana; Ilić, Nela V.; Ilić, Tihomir V.; Jeličić, Ljiljana; Sovilj, Mirjana; Martić, Vesna; Punišić, Silvana; Stokić, Miodrag (Vojnosanitetski pregled, 2023)
Background/Aim. Neurofeedback (NFB) training of sensorimotor rhythm (SMR) contributes to improving cognitive performance and increasing attention. SMR power is increased when a person is focused and task-oriented. The shorter reaction time (RT) of the P300 auditory evoked potentials (AEPs) is associated with better attention. Hence, the increase in SMR power after NFB SMR training should decrease the RT in a cognitive task. The aim of the study was to examine the ability of healthy individuals to modulate the SMR of electroencephalographic (EEG) activity between 12 and 15 Hz during 20-day NFB training sessions. In addition, the effect of NFB SMR training on RT was investigated. Methods. Participants were divided into experimental and control groups, with 24 subjects (12 males and 12 females) in each group, aged between 25 and 40 years. Participants in the experimental group were trained with authentic NFB SMR training, while in the control group, false (placebo) training was applied. AEPs were registered on five occasions: before NFB training, after 5, 10, and 20 training sessions, and one month after the last training. Results. The results showed that a series of 20 NFB SMR training sessions increased the amplitudes of the SMR. RT in the experimental group was significantly shortened, while in the control group, it was not observed. Moreover, the increase in the power of the EEG signal of the SMR showed a negative correlation with RT, but only in a subgroup of male subjects. Conclusion. The obtained results indicate the effects of NFB training on the improvement of the attention process expressed by RT.